The Evolving Higher Education Landscape in Uganda: Issues, Challenges, and Propositions - Kibuuka, Enock (International Journal of African Higher Education, 2025)
The higher education (HE) sector in Uganda is in a state of a perfect storm. As Uganda tends towards lower middle-income status and as it envisions upper middle-income status by 2040, it is beyond dispute that HE is a panacea to achieving this ambition. In order to bolster the signifcance of HE in the country’s socio-economic transformation process, higher education institutions (HEIs) in Uganda have attempted to embrace global imperatives within the broader HE discourse namely: internationalization of HE, international collaborations and knowledge transfer partnerships; revitalizing the relationship between the academic oligarchy, industry and the state; as well as strengthening the core function of HE: research, teaching and community engagement. However, an interplay of systemic defciencies, unclear institutional philosophies, and epistemological tensions have thwarted the full reformation of the country’s HE sector. By means of literature search and desk study, this paper sought to highlight the critical issues and challenges facing the country’s HE sector upon which the paper draws actionable recommendations. The article reveals that the capacity of HEIs to signifcantly contribute to the country’s development agenda is curtailed by geopolitical dynamics, autocratic rule, acute funding shortages and inadequacy of qualifed academic staﬀ. The paper recommends that HEIs should reconstruct internationalization of HE, and explore new and reliable sources of funding. Also, the paper recommends that Government should create a special loan fund for fnancing doctoral studies and also scale up university funding for research and innovations.